Hybrid RF-Energy Harvester for IoT Smart Device Applications Low Power Consumption - Nurfitri Nurfitri; Elyas Palantei; Intan Sari Areni (Universitas Medan Area, 2022)
Energy independence and long battery lifetime, the vision of 5G technology is one of them for IoT smart devices. Focusing on the challenges in this technological vision, the solution for this system is to harvest the energy sources around it as a backup or eliminate the use of batteries. The output of the hybrid energy harvester method as a solution to energy independence using radio frequency (RF) waves has been optimized in this study. The double-T patch microstrip antenna based on CSRR metamaterial as an RF energy harvester works at the ISM band frequency of 2.45 GHz and has return loss, gain and bandwidth values that are in accordance with the concept of the RF-Energy harvester system. This antenna is capable of absorbing energy using a DC converter circuit at a maximum distance of 6.79 V using 2 access points at the position of the transmitting antenna facing each other with a conversion efficiency of 6.68%. One method to maximize the output of the energy harvester is also carried out in this study by doing a hybrid with a mini solar cell, which is able to carry out constant voltage and can charge the load in the form of a cellphone. The hybrid RF-Energy harvester system designed in this research can be used as a source of energy in smart devices with small power requirements.